2013
DOI: 10.1136/gutjnl-2012-304037
|View full text |Cite
|
Sign up to set email alerts
|

A disrupted RNA editing balance mediated by ADARs (Adenosine DeAminases that act on RNA) in human hepatocellular carcinoma

Abstract: ObjectiveHepatocellular carcinoma (HCC) is a heterogeneous tumour displaying a complex variety of genetic and epigenetic changes. In human cancers, aberrant post-transcriptional modifications, such as alternative splicing and RNA editing, may lead to tumour specific transcriptome diversity.DesignBy utilising large scale transcriptome sequencing of three paired HCC clinical specimens and their adjacent non-tumour (NT) tissue counterparts at depth, we discovered an average of 20 007 inferred A to I (adenosine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
204
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(222 citation statements)
references
References 33 publications
15
204
0
Order By: Relevance
“…Thus, levels of editing in mature mRNAs may also be regulated by differential splicing. Moreover, Flnb editing has been shown to be altered in esophageal and liver carcinomas due to the increased activity of ADAR1 indicating that this enzyme may also target Flnb , at least under specific conditions [38,39]. Clearly, further investigations concerning the modulation of Flnb RNA editing will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, levels of editing in mature mRNAs may also be regulated by differential splicing. Moreover, Flnb editing has been shown to be altered in esophageal and liver carcinomas due to the increased activity of ADAR1 indicating that this enzyme may also target Flnb , at least under specific conditions [38,39]. Clearly, further investigations concerning the modulation of Flnb RNA editing will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ADAR1 and ADAR2, both, would edit the AhR 3Ј-UTR. Although a previous study (11) reported that ADAR2 is functionally expressed in normal human livers, hepatic ADAR2 protein was not detected in this study even when an antibody from another vendor was used (data not shown). Because of the lower expression level of ADAR2 compared with ADAR1, the role of ADAR2 in RNA editing in human livers may be only minor.…”
Section: Discussionmentioning
confidence: 40%
“…6B). To investigate whether the small interindividual variability in RNA editing levels in the human livers was specific for AhR, we examined the RNA editing levels in filamin B, ␤, which has been reported to be edited by ADAR1 (11). The RNA editing levels were correlated with ADAR1 p110 expression, and the interindividual variability was relatively large compared with that of AhR (Fig.…”
Section: Rna Editing Of the Ahr Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was recently reported that ADAR1 is involved in the development of liver carcinoma. 74 It will be interesting to investigate whether there is a connection between its anti-inflammatory effects and its oncogenic functions.…”
Section: Adar1 In Liver Homeostasismentioning
confidence: 99%